Pengaruh Kompetensi Dosen, Kurikulum dan Motivasi terhadap Prestasi Belajar Mahasiswa Fakultas Agama Islam STAI Laa Roiba Bogor - Ismail Mustaqim (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
This study aims to determine the effect of curriculum competence and motivation on the achievement of learning outcomes of Islamic Faculty students. The form of survey research is quantitative, namely research carried out to look for the influence of curriculum, lecturer competency and motivation on the achievement of student learning outcomes in the Faculty of Islam Tarbiyah Department Laa Roiba Islamic High School, Bogor Regency. The research method used in this study is the survey method. This study is correlational because research seeks to investigate the relationship between several research variables namely competency variables, curriculum and motivation towards learning achievement. This correlation study will use correlation and regression analysis. In this study there are three independent variables, namely competence (X1), Curriculum (X2), and motivation (X3) on the dependentvariable, namely learning achievement (Y). The three independent variables (X1, X2, and X3) are associated with the dependent variable (Y). The results of the study show that there is a positive influence between lecturer competencies (X1) on learning achievement (Y). This is indicated by the correlation coefficient of 0.921 with the significance of the tcount correlation coefficient of 3.967 and the significance of the regression coefficient F count of 51.930 which is very significant at α = 0.05. for curriculum (X2) on learning achievement (Y). There is a positive influence. This is indicated by the correlation coefficient of 0.914 with the significance of the tcount correlation coefficient of 8.547 and the significance of the regression coefficient Fcount of 51.930 which is very significant at α = 0.05, and for motivation (X3) for achievement of learning outcomes (Y). This is indicated by the correlation coefficient of 0.940with the significance of the tcount correlation coefficient of 3.189 and the significance of the regression coefficient F is 51.930 which is very significant at α = 0.05, while the results of the lecturer competency analysis (X1), curriculum (X2), and motivation (X3) are together towards the achievement of learning outcomes (Y) has a significant multiple correlation coefficient with a value of 0.858 with the significance of the multiple regression coefficient F 51.930. In this study shows the importance of variable competence of lecturers, curriculum and motivation in an effort to improve student learning achievement and it can be concluded that as an educator must have competence, understand the curriculum and provide motivation to students, student achievement will increase and vice versa if as an educator do not have good competence, do not understand the curriculum and provide less motivation to students, the achievement of learning outcomes will decrease.